Regenerative potential of mesenchymal stromal cells in wound healing: unveiling the influence of normoxic and hypoxic environments - Mahjoor, Mohamad; Fakouri, Arshia; Farokhi, Simin; Nazari, Hojjatollah; Afkhami, Hamed; Heidari, Fatemeh (Frontiers in Cell and Developmental Biology, 2023)
The innate and adaptive immune systems rely on the skin for various purposes, serving as the primary defense against harmful environmental elements. However, skin lesions may lead to undesirable consequences such as scarring, accelerated skin aging, functional impairment, and psychological effects over time. The rising popularity of mesenchymal stromal cells (MSCs) for skin wound treatment is due to their potential as a promising therapeutic option. MSCs offer advantages in terms of differentiation capacity, accessibility, low immunogenicity, and their central role in natural wound-healing processes. To accelerate the healing process, MSCs promote cell migration, angiogenesis, epithelialization, and granulation tissue development. Oxygen plays a critical role in the formation and expansion of mammalian cells. The term "normoxia" refers to the usual oxygen levels, defined at 20.21 percent oxygen (160 millimeters of mercury), while "hypoxia" denotes oxygen levels of 2.91 percent or less. Notably, the ambient O2 content (20%) in the lab significantly differs from the 2-9% O2 concentration in their natural habitat. Oxygen regulation of hypoxia-inducible factor-1 (HIF-1) mediated expression of multiple genes plays a crucial role in sustaining stem cell destiny concerning proliferation and differentiation. This study aims to elucidate the impact of normoxia and hypoxia on MSC biology and draw comparisons between the two. The findings suggest that expanding MSC-based regenerative treatments in a hypoxic environment can enhance their growth kinetics, genetic stability, and expression of chemokine receptors, ultimately increasing their effectiveness.